The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.22271/chemi.2020.v8.i6c.10765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation levels on yield, water use, water use efficiency and NPK uptake of fennel (Foeniculum vulgare Mill.) cultivars grown under drip system

Abstract: A field experiment was conducted at Instructional Farm, College of agriculture, Bikaner (Rajasthan) during rabi season to study the influence of drip irrigation levels on yield, water use efficiency and nutrient uptake of different cultivars of fennel. Results revealed that irrigation through drip at 1.0 PE recorded significantly highest number of umbels plant -1 (30.90) and number of umbellate umbel -1 (20.04). Water use was higher when crop was irrigated at 1.0 PE, where as water use efficiency was found max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The increased head yield in different cabbage varieties might have also increased dry matter production which ultimately increased the nutrient (NPK) uptake in cabbage head. Haque [11] in cabbage, Singh et al [12] in fennel and Kumari [13] in cowpea were also observed that uptake of nutrients was significantly affected with different varieties.…”
Section: Resultsmentioning
confidence: 99%
“…The increased head yield in different cabbage varieties might have also increased dry matter production which ultimately increased the nutrient (NPK) uptake in cabbage head. Haque [11] in cabbage, Singh et al [12] in fennel and Kumari [13] in cowpea were also observed that uptake of nutrients was significantly affected with different varieties.…”
Section: Resultsmentioning
confidence: 99%